Diffusely adherent Escherichia coli strains isolated from children and adults constitute two different populations - Almeida, Rosane Mansan (2013)
Background: Diffusely adherent Escherichia coli (DAEC) have been considered a diarrheagenic category of E. coli for which several potential virulence factors have been described in the last few years. Despite this, epidemiological studies involving DAEC have shown inconsistent results. In this work, two different collections of DAEC possessing Afa/Dr genes, from children and adults, were studied regarding characteristics potentially associated to virulence. Results: DAEC strains were recovered in similar frequencies from diarrheic and asymptomatic children, and more frequently from adults with diarrhea (P < 0.01) than from asymptomatic adults. Association with diarrhea (P < 0.05) was found for SAT-positive strains recovered from children and for curli-positive strains recovered from adults. Mixed biofilms involving DAEC and a Citrobacter freundii strain have shown an improved ability to form biofilms in relation to the monocultures. Control strains have shown a greater diversity of Afa/Dr adhesins and higher frequencies of cellulose, TTSS, biofilm formation and induction of IL-8 secretion than strains from cases of diarrhea in children. Conclusions: DAEC strains possessing Afa/Dr genes isolated from children and adults represent two different bacterial populations. DAEC strains carrying genes associated to virulence can be found as part of the normal microbiota present in asymptomatic children.